Research on Vibration Reduction Performance of Series Bistable Nonlinear Energy Sink - XiaoMin Jia; XiaoTong Chang; GuoDing Xue (Shock and Vibration)
The vibration reduction performance of NES is extremely sensitive to the excitation intensity. When the excitation intensity is low, target energy transfer cannot occur, and the vibration reduction performance is significantly reduced. When the excitation intensity is too high, bifurcation occurs, forming a high branching response and the performance of the NES is also significantly reduced, even leading to vibration deterioration. In response to the above issues, this paper proposes a series bistable nonlinear energy sink (SBNES), which improve the vibration reduction performance under low disturbances through chaotic response between wells, and reduce the generation of high branches within a certain range through mass configuration. The vibration reduction performance of the proposed SBNES was analyzed using analytical and numerical methods, and the results showed that it had better vibration reduction performance than CNES under both impact and harmonic excitations.